Distinguishing Tumor Admixed in a Radiation Necrosis (RN) Background: 1H and 2H MR With a Novel Mouse Brain-Tumor/RN Model - Ge, Xia; Song, Kyu-Ho; Engelbach, John A.; Yuan, Liya; Gao, Feng; Dahiya, Sonika; Rich, Keith M.; Ackerman, Joseph J. H.; Garbow, Joel R. (Frontiers in Oncology, 2022)
PURPOSE: Distinguishing radiation necrosis (RN) from recurrent tumor remains a vexing clinical problem with important health-care consequences for neuro-oncology patients. Herein, mouse models of pure tumor, pure RN, and admixed RN/tumor, are employed to evaluate hydrogen (1H) and deuterium (2H) magnetic resonance methods for distinguishing RN vs. tumor. Further, proof-of-principle, range-finding deuterium (2H) metabolic magnetic resonance is employed to assess glycolytic signatures distinguishing RN vs. tumor. MATERIALS AND METHODS: A pipeline of common quantitative 1H MRI contrasts, including an improved magnetization transfer ratio (MTR) sequence, and 2H magnetic resonance spectroscopy (MRS) following administration of 2H-labelled glucose, was applied to C57BL/6 mouse models of: (i) late time-to-onset RN, occurring 4 - 5 weeks post focal 50-Gy (50% isodose) Gamma Knife irradiation to the left cerebral hemisphere, (ii) glioblastoma, growing ~18 – 24 days post implantation of 50,000 mouse GL261 tumor cells into the left cerebral hemisphere, and (iii) mixed model, with GL261 tumor growing within a region of radiation necrosis (1H MRI only). Control C57BL/6 mice were also examined by 2H metabolic magnetic resonance. RESULTS: Differences in quantitative 1H MRI parametric values of R1, R2, ADC, and MTR comparing pure tumor vs. pure RN are all highly statistically significant. Differences in these parameter values and also DCEAUC for tumor vs. RN in the mixed model (tumor growing in an RN background) are also all significant, demonstrating that these contrasts – in particular, MTR – can effectively distinguish tumor vs. RN. In addition, quantitative 2H MRS showed a highly statistically significant dominance of aerobic glycolysis (glucose  lactate; fermentation, Warburg effect) in tumor vs. oxidative respiration (glucose  TCA cycle) in RN and control brain. CONCLUSIONS: These findings, employing a pipeline of quantitative 1H MRI contrasts and 2H MRS following administration of 2H-labelled glucose, suggest a pathway for substantially improving the discrimination of tumor vs. RN in the clinic.